Causes of death at the University of Ghana Hospital in Accra—a 37-year review (1979–2015). Issue 4 (5th April 2018) - Sutherland, Edward K; Ansa, Gloria A; Baiden, Frank; Quaye, Enoch N B; Amoabeng, Afua A; Amenuveve, Christian
Abstract: Background: An analysis of the causes of death in developing countries is needed to improve healthcare delivery. The aim of this study was to conduct a descriptive analysis of the causes of death at the University of Ghana Hospital from 1979 to 2015. Methods: Data were extracted from the electronic database of the University of Ghana Hospital. Diseases were grouped into three broad groups of causes of death as per the Global Burden of Disease cause list, with some diseases of epidemiological importance outlined and analysed by age, gender and time in years. Results: Of 3263 deaths, almost 60% were caused by non-communicable diseases (NCDs) that consisted of cancers, diabetes mellitus, cardiovascular diseases and other systemic conditions. Deaths by malaria, tuberculosis, diarrhoeal diseases and immunizable childhood diseases declined over the years while deaths from NCDs increased. The majority of cases of NCDs were due to cardiovascular disorders. Conclusions: The study suggests that Ghana has a double burden of disease with predominantly NCDs from cardiovascular diseases, metabolic disorders and cancers. Although malaria and other childhood-related illnesses have declined significantly, human immunodeficiency virus is fuelling the communicable disease mortalities. There is an urgent need to scale up NCD control interventions while strengthening communicable disease control.